Children’s Body Type Discrimination Model and Prototype Paper Pattern Automatic Generation Model Analysis (Journal of Fiber Bioengineering and Informatics, 2024)
With the growing demand for personalized clothing, the children’s apparel market is receiving significantattention. Traditional pattern-making methods often fail to accommodate the diverse body shapes andpreferences of preschoolers, negatively impacting consumer satisfaction. Although existing studies haveexamined various pattern-making techniques, they frequently overlook the unique needs of children,resulting in limited customization options and reduced efficiency. Therefore, a comprehensive approachis necessary to effectively integrate body size data with personalized pattern-making rules. This studyinvestigates a parameterized model for generating personalized children’s clothing paper patterns. It aimsto streamline the production process while catering to personalised preferences. Through the analysisof preschooler body size data, 24 body type features are identified, leading to the development of adiscrimination model based on principal component analysis and support vector machine. This model,integrated with clothing pattern-making rules, enhances the structure of paper patterns. Furthermore, aparameterised paper pattern for children’s clothing is created, utilizing children’s body data to generatetailored paper patterns efficiently. Additionally, a linkage model combining 3D and 2D aspects isemployed to evaluate clothing fit and overall effects through virtual try-on simulations. Findings suggestreduced production complexity, time, and improved efficiency and quality in personalized pattern making.
Keywords: Body Type Discrimination Model; Children’s Clothing Prototype; Pattern Generation; Grasshopper Parameterization; Virtual Fitting.